Análisis comparativo de tecnologías de interfaz natural de usuario: caso de estudio Reconocimiento de Voz y Gestos - Lliguin Pilliza, Erick Andrés (2022)
At present research work, a comparative analysis of Natural User Interface (NUI) technologies is carried out, the case study being the process of voice and gesture recognition, this proposal is aimed at contributing to the knowledge about NUI that students of Information Systems career of Technical University of Cotopaxi. It is part of a bibliographic review process on which it was possible to establish the most relevant characteristics to consider in the implementation of systems that incorporate functionalities capable to interact with users without the need to manipulate the mouse or keyboard, at the same way a prototype through the application of agile practices to demonstrate feasibility to incorporate functionalities with voice recognition and/or gestures. Python, Visual Studio Code code editor, Google's Speech Recognition libraries and OpenCV were used as programming language. It should be noted that Python turns out to be the most widely used programming language worldwide and also provides superior features to other languages to work with Natural User Interfaces. For the comparative analysis, tables were designed where technical criteria are included with the characteristics of working with voice recognition or gesture recognition can be identified, however it can be concluded that voice recognition is currently more used since There are already different applications that incorporate this type of functionality.